2011
DOI: 10.1002/eco.157
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration partitioning in semiarid shrubland ecosystems: a two‐site evaluation of soil moisture control on transpiration

Abstract: Vegetation of dryland ecosystems is sensitive to precipitation pulses. Future climate scenarios suggest that the frequency and magnitude of precipitation events will change. How much and to what extent will these changes impact the hydrological cycle in creosotebush (Larrea tridentata) shrublands that dominate the three North American hot deserts? In this study, we examine the partitioning of precipitation inputs into bare soil evaporation (E) and transpiration (T) within creosotebush ecosystems at sites chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(117 citation statements)
references
References 57 publications
9
106
2
Order By: Relevance
“…However, uptake of water and nutrients need not be tightly coupled (Pate et al, 1998). While some plant species rely mainly on deep soil moisture for transpiration (Kurc and Small, 2007;Kurc and Benton, 2010;Cavanaugh et al, 2011), their nutrient uptake may be uncoupled from this water uptake if the nutrients are only present in shallow soil or near decomposing leaf litter. On the other hand, significant pools of some nutrients may be found in deeper soil layers closer to unweathered bedrock (McCulley et al, 2004;Maeght et al, 2013).…”
Section: Hypothesis 6 Trees Grow the Majority Of Their Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, uptake of water and nutrients need not be tightly coupled (Pate et al, 1998). While some plant species rely mainly on deep soil moisture for transpiration (Kurc and Small, 2007;Kurc and Benton, 2010;Cavanaugh et al, 2011), their nutrient uptake may be uncoupled from this water uptake if the nutrients are only present in shallow soil or near decomposing leaf litter. On the other hand, significant pools of some nutrients may be found in deeper soil layers closer to unweathered bedrock (McCulley et al, 2004;Maeght et al, 2013).…”
Section: Hypothesis 6 Trees Grow the Majority Of Their Rootsmentioning
confidence: 99%
“…For example, some stable isotope studies (e.g., Phillips and Ehleringer, 1995) and sap flow measurements linked with soil moisture measurements at depth (e.g., Cavanaugh et al, 2011) have identified cases in which plants with roots mostly near the surface still rely mainly on deep soil moisture for transpiration. For those systems, we infer that the shallow roots are grown densely to provide growth-limiting nutrients; however, such an inference should be tested.…”
Section: Hypothesis 6 Trees Grow the Majority Of Their Rootsmentioning
confidence: 99%
“…In situ observations have allowed for investigation into how different environmental factors control soil drying rates and thus evaporation rates (Cavanaugh et al, 2011;Detto et al, 2006;e.g., Kurc andSmall, 2004, 2007). Only recently has satellite remote sensing of soil moisture advanced sufficiently to make it possible to monitor drying rates on a large scale (Entekhabi et al, 2010;Kerr, 2006), thus allowing scientists to evaluate the physical controls on soil drying across a wider range of conditions.…”
Section: P J Shellito Et Al: Controls On Surface Soil Drying Ratesmentioning
confidence: 99%
“…In situ observations have allowed for investigation of how different environmental factors control soil drying rates and thus evaporation rates (Cavanaugh et al, 2011;Detto et al, 2006;e.g., Kurc andSmall, 2004, 2007). Only recently has satellite remote sensing of soil moisture advanced sufficiently to make it possible to monitor drying rates at large scales (Entekhabi et al, 2010;Kerr, 2006), thus allowing scientists to evaluate the physical controls on soil drying across a wider range of 15 conditions.…”
mentioning
confidence: 99%